Love, Honour and God : Pashto Writings of Early Modern Times - Pelevin, Mikhail, (Iran and the Caucasus Monographs ;, 2025)
Love, Honour and God tells about the talented and determined people who challenged the dominance of the Persophone written culture and created literature in their mother tongue, Pashto. Offering insights into the lives and literary accomplishments of many acclaimed and less known Pashtun authors of the early modern period, this book traces the development of Pashto writings from around 1530 to 1830 as a considered pursuit of an educational mission and a verbal affirmation of ethnic identity. Based primarily on original texts in Pashto verse and prose, the book explores social views, aesthetic preferences and spiritual values that underlie modern ideologies and cultural awareness of Pashto-speaking communities in Afghanistan and Pakistan.